Quench and stability of Roebel cables at 77 K and self-field: Minimum quench power, cold end cooling, and cable cooling efficiency. (October 2018) - Kovacs, C.J.; Majoros, M.; Sumption, M.D.; Collings, E.W.
Highlights: Pulses at variable I / Ic resulted in stability modes unlike that seen in LTS. 3 modes were created: sub-current-sharing, standing normal zone, and slow quench. MQP is the property of interest for stability in HTS magnets. Abstract: A 9-tape, 14 mm wide ReBCO Roebel cable was soldered onto a U-shaped holder. The critical current, Ic, was measured at 77 K and self-field. The cryostability of the cable was studied in response to the application of local pulses of 1–14 W at several values of i = I/Ic . A detailed analysis of the cable's cryostability was presented. With a Stekly parameter α  =  G/Q  « 1 and a heat generation margin of ∼190 kW/m 2 the present ReBCO cable was shown to be ultra cryostable with respect to internally generated transport-current overload. However, the cable was much less stable against externally and locally applied disturbances because of the tendency to initiate local film boiling. A locally applied 10 W led to a prediction of a film-boiling-cooled zone with a temperature of 181 K. However, when cold-end cooling was considered, the predicted hot spot temperature decreased to 87–115 K depending on the surface-cooling efficiency. Predictions were compared to experiment extracting a cooling efficiency parameter representing the penetration of the cryogen into the cable. Experiment showed the generation of time stable normal zones which were a function of disturbance power. This led to the description of the cable stability in terms of minimum quench power; the results are presented in stability diagrams.